LABOR RESOURCES AND LABOR UTILIZATION IN VINH CITY, NGHE AN PROVINCE IN THE PERIOD 2012-2022 - Phan Thi Van (Tạp chí Khoa học)
Labour resources and employment are top concerns in the socio-economic development strategies of every country and locality on the path of development. This article analyses and clarifies the current state of labour resources and employment in Vinh City by employing synthesis analysis, field surveys, and expert consultation. Based on this analysis, several solutions are proposed to enhance the quality and rational use of labour resources to meet the current demands of industrialization and modernization. The research results provide a critical foundation for management agencies in formulating development strategies related to population and social issues in Vinh City and serve as a valuable resource for teaching local geography.